Olfactory Stimuli Increase Presence in Virtual Environments. - Benson G Munyan; Sandra M Neer; Deborah C Beidel; Florian Jentsch (PLoS ONE, 2016)
BACKGROUND:Exposure therapy (EXP) is the most empirically supported treatment for anxiety and trauma-related disorders. EXP consists of repeated exposure to a feared object or situation in the absence of the feared outcome in order to extinguish associated anxiety. Key to the success of EXP is the need to present the feared object/event/situation in as much detail and utilizing as many sensory modalities as possible, in order to augment the sense of presence during exposure sessions. Various technologies used to augment the exposure therapy process by presenting multi-sensory cues (e.g., sights, smells, sounds). Studies have shown that scents can elicit emotionally charged memories, but no prior research has examined the effect of olfactory stimuli upon the patient's sense of presence during simulated exposure tasks. METHODS:60 adult participants navigated a mildly anxiety-producing virtual environment (VE) similar to those used in the treatment of anxiety disorders. Participants had no autobiographical memory associated with the VE. State anxiety, Presence ratings, and electrodermal (EDA) activity were collected throughout the experiment. RESULTS:Utilizing a Bonferroni corrected Linear Mixed Model, our results showed statistically significant relationships between olfactory stimuli and presence as assessed by both the Igroup Presence Questionnaire (IPQ: R2 = 0.85, (F(3,52) = 6.625, p = 0.0007) and a single item visual-analogue scale (R2 = 0.85, (F(3,52) = 5.382, p = 0.0027). State anxiety was unaffected by the presence or absence of olfactory cues. EDA was unaffected by experimental condition. CONCLUSION:Olfactory stimuli increase presence in virtual environments that approximate those typical in exposure therapy, but did not increase EDA. Additionally, once administered, the removal of scents resulted in a disproportionate decrease in presence. Implications for incorporating the use of scents to increase the efficacy of exposure therapy is discussed.